2018
DOI: 10.1021/acscatal.8b01014
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atomic Cu with Multiple Oxygen Vacancies on Ceria for Electrocatalytic CO2 Reduction to CH4

Abstract: The electrocatalytic reduction of CO2 into value-added chemicals such as hydrocarbons has the potential for supplying fuel energy and reducing environmental hazards, while the accurate tuning of electrocatalysts at the ultimate single-atomic level remains extremely challenging. In this work, we demonstrate an atomic design of multiple oxygen vacancy-bound, single-atomic Cu-substituted CeO2 to optimize the CO2 electrocatalytic reduction to CH4. We carried out theoretical calculations to predict that the single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
451
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(467 citation statements)
references
References 42 publications
16
451
0
Order By: Relevance
“…Ethylene (C 2 H 4 ), an important raw material, is one of the main C2 products over Cu electrodes . However, due to the simultaneous production of H 2 and other C1 species (i.e., CO, CH 4 ), the Faradaic efficiency for the production of C 2 H 4 (FE C2H4 ) on metallic Cu is usually low . Efforts to improve the FE C2H4 of Cu‐based catalysts have focused on optimizing the sizes, morphologies, and exposed crystal facets of metallic Cu NPs .…”
mentioning
confidence: 99%
“…Ethylene (C 2 H 4 ), an important raw material, is one of the main C2 products over Cu electrodes . However, due to the simultaneous production of H 2 and other C1 species (i.e., CO, CH 4 ), the Faradaic efficiency for the production of C 2 H 4 (FE C2H4 ) on metallic Cu is usually low . Efforts to improve the FE C2H4 of Cu‐based catalysts have focused on optimizing the sizes, morphologies, and exposed crystal facets of metallic Cu NPs .…”
mentioning
confidence: 99%
“…Wang et al proposed the design of multiple oxygen vacancies formation by doping single atomic Cu metal (4% doping level) into Ce nanorods to optimize CO 2 RR to CH 4 , attaining a FE CH4 of 58% at −1.8 V with good stability ( Figure 11 ). Moreover, as indicated in Figure , variation in Cu doping level can alter the product selectivity of CO 2 RR. Moreover, theoretical DFT calculations further confirmed that three‐oxygen vacancies bound Cu structure could efficiently activate CO 2 and convert it to CH 4 (Figure c–g).…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 92%
“…Data from refs. . The detailed catalytic activity of these catalysts is presented in Table S3 (Supporting Information).…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 :Ru with Ti 3+ and Ru 5+ achieved high H 2 evolution reaction activity with appropriate H 2 adsorption Gibbs free energies. In mesoporous CeO 2 nanorods, substitution of single Cu atoms in the CeO 2 (110) surface can stably enrich up to three oxygen vacancies around each Cu site; this phenomenon yields a highly effective catalytic center for CO 2 adsorption and activation …”
Section: Applications Of Nonsimpmsmentioning
confidence: 99%